2004
DOI: 10.1002/nur.20056
|View full text |Cite
|
Sign up to set email alerts
|

Group‐based HIV risk reduction intervention for adolescent girls: Evidence of feasibility and efficacy

Abstract: The purposes of this pilot study were (a) to assess the feasibility of a community-based, small group HIV risk reduction intervention with adolescent girls, and (b) to obtain preliminary evidence of the efficacy of this theoretically-guided intervention using a controlled design. The feasibility of the intervention was demonstrated by successfully implementing it with 33 sexually-active, single girls. Preliminary evidence of the efficacy of the intervention was obtained using a randomized trial with 62 sexuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(71 citation statements)
references
References 49 publications
0
70
1
Order By: Relevance
“…Such effects were larger to the extent that interventions included greater amounts of condom skills-training and included more motivational training. Contrary to other reviewers’ conclusions that intervention dosage does not matter, 108 the current results found that maximal efficacy results from interventions sessions that provide condom skills and motivational training per session (e.g., 1 hour 17, 7374 ). These patterns did not hinge on the number of sessions interventions had.…”
Section: Commentcontrasting
confidence: 99%
See 2 more Smart Citations
“…Such effects were larger to the extent that interventions included greater amounts of condom skills-training and included more motivational training. Contrary to other reviewers’ conclusions that intervention dosage does not matter, 108 the current results found that maximal efficacy results from interventions sessions that provide condom skills and motivational training per session (e.g., 1 hour 17, 7374 ). These patterns did not hinge on the number of sessions interventions had.…”
Section: Commentcontrasting
confidence: 99%
“…Use of these criteria resulted in 67 independent studies including 9 studies containing supplemental information (e.g., intervention details, outcomes from follow-up assessments), which included 98 separate interventions and sampled 51,240 participants. 17, 1993 Each intervention was treated as an individual study (see supplemental figure). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants who consented and attended the intervention or control sessions (n = 62) were compared with the participants who consented but did not attend any intervention or control sessions (n = 67) on all demographic, risk behavior, and antecedent variables. These analyses revealed no differences between groups for the following variables: demographics (age, race, hours worked per week, risk behavior, pregnancy history, and STI history), HIV-related knowledge, motivation (risk perception, readiness to change, behavioral intentions, pros and cons of condom use), behavioral skills (confidence in condom use), and sexual risk behaviors (Morrison-Beedy et al, 2005).…”
Section: Retention Protocol Developmentmentioning
confidence: 95%
“…Laumann et al (1994) found that older respondents and those with less education were less likely to have experienced oral sex. In Canadian studies, oral sex has been mainly studied among youth ( Barrett, 2004;McKay, 2004;Morrison-Beedy, Corey, Kowalski, & Tu, 2005). The COMPAS survey was the first to ask a random sample of Canadian adults about their experience with oral sex.…”
Section: Introductionmentioning
confidence: 99%